IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA MATERI SIFAT-SIFAT CAHAYA TERHADAP KEAKTIFAN SISWA KELAS 5 SD NEGERI LAMPER LOR KOTA SEMARANG - Salsabila Rifa Khairunnisa; Yunita Sari, Nuhyal Ulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research discusses the implementation of Culturally Responsive Teaching (CRT) approach in learning Natural and Social Sciences (IPAS) at SDN Lamper Lor, especially on the properties of light. This research is motivated by the low activeness of students due to conventional learning methods that are teacher-centered and do not consider the cultural background of students. The purpose of this study is to examine how the CRT approach can be integrated in teaching IPAS to increase learner participation. This research used a qualitative case study design involving one teacher and 25 Grade 5 learners of SD Negeri Lamper Lor with diverse backgrounds. Data were collected through participatory observation, in-depth interviews, and document analysis. Based on the results of the study, the use of the CRT approach can increase the activeness of learners by 84% actively answering and responding to questions from the teacher. 76% of learners were fully involved in group work when conducting simple experiments on light reflection and refraction. And 86% of learners dare to ask questions and tell their personal experiences. Based on the results of the study, it can be said that the CRT approach is able to provide an increase in the activeness of students in elementary schools in the subject of Natural and Social Sciences (IPAS).